Toxoplasma gondii dense granule protein 3 promotes endoplasmic reticulum stress-induced apoptosis by activating the PERK pathway - Cudjoe Obed; Minmin Wu; Ying Chen; Ran An; Haijian Cai; Qingli Luo; Li Yu; Jie Wang; Fang Liu; Jilong Shen; Jian Du (Parasites & Vectors, 2022)
Abstract Background Toxoplasma gondii is a neurotropic single-celled parasite that can infect mammals, including humans. Central nervous system infection with T. gondii infection can lead to Toxoplasma encephalitis. Toxoplasma infection can cause endoplasmic reticulum (ER) stress and unfolded protein response (UPR) activation, which ultimately can lead to apoptosis of host cells. The dense granule protein GRA3 has been identified as one of the secretory proteins that contribute to the virulence of T. gondii; however, the mechanism remains enigmatic. Methods The expression of the GRA3 gene in RH, ME49, Wh3, and Wh6 strains was determined using quantitative real-time polymerase chain reaction (qRT–PCR). pEGFP-GRA3Wh6 was constructed by inserting Chinese 1 Wh6 GRA3 (GRA3Wh6) cDNA into a plasmid encoding the enhanced GFP. Mouse neuro2a (N2a) cells were transfected with either pEGFP or pEGFP-GRA3Wh6 (GRA3Wh6) and incubated for 24–36 h. N2a cell apoptosis and ER stress-associated proteins were determined using flow cytometry and immunoblotting. Furthermore, N2a cells were pretreated with GSK2656157 (a PERK inhibitor) and Z-ATAD-FMK (a caspase-12 inhibitor) before GRA3Wh6 transfection, and the effect of the inhibitors on GRA3Wh6-induced ER stress and apoptosis were investigated. Results GRA3 gene expression was higher in the less virulent strains of type II ME49 and type Chinese 1 Wh6 strains compared with the virulent strains of type I RH strain and type Chinese 1 Wh3 strain. Transfection with GRA3Wh6 plasmid induced neuronal apoptosis and increased the expression of GRP78, p-PERK, cleaved caspase-12, cleaved caspase-3, and CHOP compared with the control vector. Pretreatment with GSK2656157 and Z-ATAD-FMK decreased apoptosis in N2a cells, and similarly, ER stress- and apoptosis-associated protein levels were significantly decreased. Conclusion GRA3 induces neural cell apoptosis via the ER stress signaling pathway, which could play a role in toxoplasmic encephalitis. Graphical Abstract